Design, development, and optimization of mucoadhesive buccal films of ganaxolone for enhanced bioavailability - Pawar, Onkar; Godge, Rahul; Shinde, Ganesh; Barde, Kailas; Vikhe, Akshay (Journal of Applied Pharmaceutical Research, 2025)
Background: CDD disorder affects children mainly during their first three months of life. The buccal route offers advantages over oral administration for ganaxolone by avoiding first-pass metabolism and providing direct systemic absorption. This study aimed to formulate and characterise mucoadhesive buccal films of ganaxolone to increase its bioavailability. Methods: Mucoadhesive buccal films were prepared using a solvent casting technique employing HPMC K4M and Moringa gum as polymers. The formulation was optimized using a 32-factorial design, where polymer concentrations were varied systematically to achieve optimal film properties. Nine batches (OF1-OF9) were formulated and evaluated for various physicochemical parameters, mucoadhesive strength, percentage drug content, goat buccal mucosa permeation study, and stability analysis. Results: Based on the findings, the OF8 batch containing optimal polymer ratio (250mg HPMC K4M and 60mg Moringa gum) emerged as the superior formulation with 94.45±0.34% drug content, 15.37±0.58 N/mm² tensile strength, and 7.8±0.57 N mucoadhesive strength. Permeation studies consequently confirmed 96.37% of the drug at 8 hours with a 13.63 µg /cm² /h permeation rate. There was no evidence of drug-excipient interaction in FTIR and DSC analysis. The formulation was set to be stable for 6 months at accelerated conditions (40±2°C, 75±5% RH) with an average tensile strength above 15 N/mm² and an average ex-vivo drug permeation of 93%. Conclusion: This optimized buccal film formulation demonstrates promising potential for clinical application in CDD treatment by offering enhanced bioavailability, controlled release, and patient-friendly administration, which is particularly beneficial for pediatric patients.